A hydrogen-sensing multiprotein complex controls aerobic hydrogen metabolism in Ralstonia eutropha. (1st February 2005) - Friedrich, B.; Buhrke, T.; Burgdorf, T.; Lenz, O.
Abstract : H2 is an attractive energy source for many microorganisms and is mostly consumed before it enters oxic habitats. Thus aerobic H2 -oxidizing organisms receive H2 only occasionally and in limited amounts. Metabolic adaptation requires a robust oxygen-tolerant hydrogenase enzyme system and special regulatory devices that enable the organism to respond rapidly to a changing supply of H2 . The proteobacterium Ralstonia eutropha strain H16 that harbours three [NiFe] hydrogenases perfectly meets these demands. The unusual biochemical and structural properties of the hydrogenases are described, including the strategies that confer O2 tolerance to the NAD-reducing soluble hydrogenase and the H2 -sensing regulatory hydrogenase. The regulatory hydrogenase that forms a complex with a histidine protein kinase recognizes H2 in the environment and transmits the signal to a response regulator, which in turn controls transcription of the hydrogenase genes.